IMPLEMENTASI METODE MUROJA'AH HARIAN DALAM MENJAGA HAFALAN AL-QUR’AN SANTRI DI RUMAH QUR’AN SABIILUL MUHTADIIN KOTA JAMBI - Hasanah, Nurul; Hafiq (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of the daily muroja'ah method in maintaining students' memorization of the Qur'an. The daily muroja'ah method is an important strategy in the memorization process to maintain and sustain the fluency and accuracy of memorization. This is a qualitative study. Data collection was conducted through observation, interviews, and documentation. The results show that the daily muroja'ah method is applied routinely and in a structured manner through repetition of previous memorization sessions conducted with the teacher. This method is effective in maintaining the quality of students' memorization and minimizing forgetfulness. Thus, the daily muroja'ah method can be used as a strategic effort to maintain students' memorization of the Qur'an.